High Protein Milk Affected the Increase of the Hb Levels of Third-trimester of Pregnancy with Anemia - Dian Mayasari; Ratih Mega Septiasari; Ita Nurfadilah (STIKes Patria Husada Blitar, 2024)
Anemia is a risk factor that contributes to 50% of all maternal deaths. The main factors causing anemia are low iron intake and infection. Protein intake, especially animal protein intake, helps increase iron absorption. This study aims to determine the effect of providing high protein milk intake on increasing hemoglobin levels in pregnant women in the third trimester with iron deficiency. This type of research is Pre-Experimental with One Group Pretest-Posttest Design. The population in this study was all third-trimester of pregnant women with pale faces in the of the Gondanglegi Public Health Center Kabupaten Malang. The sample was 33 people taken by using the total sampling technique. The measuring test was the Wilcoxon Marked Rank Test. The examination results showed that the average hemoglobin level before treatment was 10.1 gr/dl, and after treatment was 11.1 gr/dl. The results showed that there was an effect of giving high-protein milk on increasing hemoglobin levels in third-trimester pregnant women with pale skin in Gondanglegi Health Center (p-value = 0.000). This study concludes that milk protein consumption basically affects the increase in hemoglobin levels in pregnant women. It is recommended for pregnant women who get anemia to focus on their food intake, especially protein consumption.